Pengaruh Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Pegawai Pada Dinas Koperasi dan UMKM Kabupaten Bima - Adelia Indah Wati; Muhammad Yusuf (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Non-physical work environment is one aspect that must be considered in an agency because this will affect job satisfaction. A poor non-physical work environment is feared that it can reduce employee job satisfaction so that the work done will feel unpleasant to complete. This study aims to determine and analyze the effect of non-physical work environment on employee job satisfaction at the Bima Regency Cooperative and UMKM Office. This research is associative type. The population used was as many as 31 respondents using saturated sampling techniques so that the sample in this study was the entire population of 31 respondents. The research instrument used was a Likert scale questionnaire with data analysis techniques validity test, reliability test, simple regression analysis, simple correlation analysis, hypothesis testing (T test) and determination test. Based on the results of this study concluded that the non-physical work environment has a significant effect on employee job satisfaction at the Bima Regency Cooperative and UMKM Office. This is evidenced by the t test value of 14,829 and sig 0,000. The determinant test shows that job satisfaction is influenced by the non-physical work environment by 98%, while the remaining 8% is influenced by other factors not included in this study